Limiting pump intensity for sulfur-doped gallium selenide crystals - Guo, Jin; Li, Dian-Jun; Xie, Ji-Jiang; Zhang, Lai-Ming; Feng, Z.-S; Andreev, Yury M. 1946-; Kokh, Konstantin A.; Lanskii, Grigory V.; Potekaev, Aleksandr I. 1951-; Shaiduko, Anna V.; Svetlichnyi, Valerii A. (Laser physics letters)
High optical quality undoped and sulfur-doped gallium selenide crystals were grown from melts by the modified vertical Bridgman method. Detailed study of the damage produced under femtosecond pulse exposure has shown that evaluation of the damage threshold by visual control is unfounded. Black matter spots produced on crystal surfaces do not noticeably decrease either its transparency or its frequency conversion efficiency as opposed to real damage identified as caked well-cohesive gallium structures. For the first time it was demonstrated that optimally sulfur-doped gallium selenide crystal possesses the highest resistivity to optical emission (about four times higher in comparison with undoped galliumselenide).